2010
DOI: 10.1152/ajpregu.00480.2009
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric contraction induces inflammatory responses in rat skeletal muscle: role of tumor necrosis factor-α

Abstract: Eccentric contraction (EC) is known to elicit inflammation and damage in skeletal muscle. Proinflammatory cytokine TNF-alpha plays an important role in this pathogenesis, but the time course of its response to EC and the regulatory mechanisms involved are not clear. The purpose of the study is twofold: 1) to investigate the gene expression of TNF-alpha in rat muscle during and after an acute bout of downhill running and the associated oxidoreductive (redox) changes; and 2) to examine whether EC activates muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 53 publications
6
53
3
1
Order By: Relevance
“…The upregulation of TNF-␣ mRNA expression found in our study supports data from other investigations in rats (23) and humans (5), emphasizing the systemic proinflammatory response after eccentric exercise (31). However, TG presented a reduction in TNF-␣ mRNA abundance after the second bout, which would indicate that the eccentric training protocol mediated the downregulation of TNF-␣ mRNA levels.…”
Section: Discussionsupporting
confidence: 91%
“…The upregulation of TNF-␣ mRNA expression found in our study supports data from other investigations in rats (23) and humans (5), emphasizing the systemic proinflammatory response after eccentric exercise (31). However, TG presented a reduction in TNF-␣ mRNA abundance after the second bout, which would indicate that the eccentric training protocol mediated the downregulation of TNF-␣ mRNA levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, strenuous exercise can alter the inXammatory function and it has been related to the pathogeny of the muscular hurts and of the systemic inXammation (Tidball 2005;Gleeson 2007;Funes et al 2011). For these reasons, in this type of exercise is important to reduce both oxidative stress and the inXammatory response, at least theirs negative aspects (Liao et al 2010;Funes et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a potential beneWcial eVect of exercise may be due to an IL-6-mediated reduction in TNF-expression and a concomitant avoidance of a low-grade inXammation state (Adser 2011). The reason of this beneWcial eVect is due to that TNF-seems to play an important role in the damage in skeletal muscle by the inXammation associated with strenuous exercise (Liao et al 2010). TNF-is a key citokyne promoting both peripheral muscle proteolysis and whole-body immune responses (Tidball 2005;Liao et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that IL-6 acts as an energy sensor, exhibiting local and endocrine metabolic effects (278,279). IL-6 and other cytokines such as IL-8, cyclooxygenase2, and TNF-a are significantly activated after unaccustomed muscle contractions, which cause microdamage to sarcomeres (54,208). The repair of the damage by satellite cells is crucial, as these cells divide and fuse to form myotubes.…”
Section: Exercise-induced Inflammation and Rosmentioning
confidence: 99%